(untitled) (Pashupati Pragya पशुपति प्रज्ञा, 2026)
For decades, the issue of Dalit landlessness has been made an important subject of debate in academic and political arena in Nepal where the specific problem of Dalit landless is perceived that the result of a conspiracy by the Hindu state based on the doctrines of pollution and purity. Land is taken as a dominant productive resource in agricultural society, and it determines the power, prestige, and property status of every individual and family which is considered a means of empowerment, economic strengthening, employment, and dignity in Nepalese society. In Nepal, fundamentally, the problem of acute landlessness is especially attached to the Dalit community, where millions of Dalits have been excluded from access of land rights due to the state’s unscientific land distribution policy and practices. Based on a survey of Dalit household respondents, this study explores how the caste system influences the status of land ownership and how it accesses and controls the socioeconomic power structures in Nepalese society. This study also examines how the root cause of landlessness has forced millions of Dalits to tackle several issues, such as food insecurity, extreme poverty, illiteracy, and social isolation at own their society. The state brought many policies and programs and formed many land-related commissions and committees for the purpose of justifiable land distribution to the landless Dalit and non-Dalit family and scientific land reform program in the democratic period, the Panchayat (party-less regime), and after the restoration of democracy, from 1990 to onwards. Unfortunately, neither the state nor the political parties seem honest and responsible for the implementation of those constitutional and legal policies and programs yet. As second-class citizens, around half of the Dalit population have been living in Nepal as squatters, Haruwa, Charuwa, Haliya, Khaliya, etc., in a purely landless and nearly landless condition. Ultimately, they have an emerging distrust of both political parties and the state, which is a possible cause for increasing tension between the state and the Dalit community.